THE IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) IN GUIDING STUDENTS’ CRITICAL THINKING - Anggi Kharisma Dewi (Journal of English Education Program (JEEP), 2014)
This paper was aimed at finding out the process of the implementation of Problem-Based Learning (PBL) in guiding students’ critical thinking, the lecturer's beliefs toward the use of Problem-Based Learning (PBL) in guiding students' critical thinking, and the students' perception toward the use of Problem-Based Learning (PBL) in guiding their critical thinking. This study employed a qualitative study that was designed as a case study. The writer took the third grade students of English education program of a private university in West Java that consisted of thirty-four students and a lecturer as a sample purposively. The findings revealed that there are several stages that can guide the students’ critical thinking and encourage the effective teaching and learning process. Moreover, the role of the lecturer in PBL class is just as a facilitator who encourages the students to use their thinking totally. Furthermore, the lecturer believed that he has opportunities to guide the students’ critical thinking. In addition, generally the students perceive that their critical thinking have been guided since they have been taught by means of Problem-Based Learning (PBL). However, in that process the students and the lecturer still find challenge; particularly it is caused by the lack of information. Based on these findings, it is recommended that the lecturer should implement the appropriate method to conduct the teaching and learning process in order to guide students’ critical thinking; moreover to create an effective teaching and learning process. Key words:    Problem-based learning (PBL), lecturer’s beliefs, students’ perception.